The nature explorer's drawing guide for kids : step-by-step lessons for observing and drawing animals, plants, and insects - Woodard, Krystal; Woodard, Brad (Rocky Nook Inc., 2023)
Spark imagination and creativity with this interactive guidebook with step-by-step drawing lessons and fascinating facts about nature! Perfect for curious explorers and aspiring artists, this beginning drawing book will show kids how to observe and draw their favorite animals and the natural world in a fun, interactive style! Popular YouTube drawing instructor Brad Woodard, founder of the Brave Kids Art Club show, shares his easy-to-follow lessons and tips and tricks for getting outside and drawing cool stuff.